MODEL PEMBELAJARAN SEJARAH DENGAN MENGINTEGRASIKAN NILAI DAN KARAKTER RELIGIUS MELALUI TEKNIK KLARIFIKASI NILAI - Muhamad Arif (TARBIYA: Journal of Education in Muslim Society, 2014)
Abstract: This research was conducted in order to find the teaching of history model that is integrated with the character of religious values ​​through values ​​clarification techniques. Given the results of the study are expected in the form of a draft model of learning, the study was conducted using the method of literature study. There are three points of major concern in this research. First, study the history of the learning materials that will be used as the basis for the development of the model at the same goal of learning, namely the material "Declaration of Independence and the Establishment of the Republic of Indonesia". Secondly, the study of the concept of didactic and methodical which allows to integrate historical material with the value and character of religion. In this case the researchers choose values ​​clarification techniques. Third, the study of religious values ​​that will be integrated in the teaching of history. In this case the value and character of the struggle, discipline in time, independent, strong stance, deliberation to reach consensus, and the unity and integrity. The process of analysis and synthesis of these components produce a learning model by integrating historical and religious character values ​​through values ​​clarification techniques. DOI: 10.15408/tjems.v1i1.1120